Corticotropin releasing hormone is present in the feline placenta and maternal serum - Watt, Madison; Mohammadzadeh, Pardis; Pinsinski, Emma; Hollinshead, Fiona K.; Bouma, Gerrit J. (Frontiers in Endocrinology, 2023)
Background: In women, placental corticotropin releasing hormone (CRH) can be detected in maternal blood throughout pregnancy and is important in the regulation of the timing of parturition. However, its role in other mammalian species is unclear. In fact, very little is known about the presence and localization of CRH in placentas other than human. In this study we report for the first time the presence of CRH in feline placenta and maternal serum. Methods: Presence of CRH mRNA and protein was assessed using RT-PCR and Western blot, respectively, in at term domestic cat placentas opportunistically obtained at a local animal shelter and spay clinic. In addition, CRH localization within the placenta was demonstrated via immunohistochemistry. Finally, presence of CRH in maternal blood from early (<21 days) and mid (25-35 days) stages of pregnancy was investigated by ELISA. Results: CRH mRNA and protein were detected in feline placentas, and localized to larger decidual cells and fetal trophoblast cells, including the binucleate cells. CRH was detectable in maternal blood collected from early-stage pregnancies, and amounts significantly increased in mid-gestation samples. Conclusion: This is the first report on the presence and localization of CRH in the feline placenta, and its increase in maternal serum during the first half of pregnancy. These data lay the foundation for future studies to determine if CRH can be used as potential novel marker for early pregnancy diagnosis, determination, and monitoring in felids, and could greatly increase efficiency and success in zoo breeding programs utilizing artificial reproductive technologies for endangered feline species.